Cushing's syndrome: Consequences of late diagnosis after bariatric surgery - Pedro, J (2020)
Prior to bariatric surgery, endocrine causes of obesity must be excluded. The diagnosis of osteoporosis in a male requires the study of secondary causes of this condition. The diagnostic delay of Cushing's syndrome may have irreversible consequences.